Desistance and Disabled Masculine Identity: Exploring the Role of Serious Violent Victimization in the Desistance Process - Green, Cherrell (Journal of developmental and life-course criminology, 2019)
Purpose: This manuscript proposes a theoretical model that will explain how violently acquired impairments (VAI) can serve as a turning point in the life-course of active male offenders or lead to further entrenchment in criminal lifestyles. Here, VAI refers to any form of physical impairment acquired as a result of interpersonal violence that limits a person’s mobility or ability to perform basic physical activities. Methods: By examining the intersections among gender, disability, and life-course criminology, the proposed model will explain how men reconstruct their disabled masculine identity following VAI. Results: In doing so, I argue that these ‘new’ identities following VAI can facilitate persistence in offending or desistance from crime. Conclusions: This theoretical model will contribute to the literature by describing the many ways in which men perform masculinity and providing a more nuanced discussion of how serious violent victimization can alter the life-course of male offenders.